Changes in H-Reflex Recruitment After Trans-Spinal Direct Current Stimulation With Multiple Electrode Configurations - Kuck, Alexander; Stegeman, Dick F.; van der Kooij, Herman; van Asseldonk, Edwin H. F. (Frontiers in Neuroscience, 2018)
Trans-spinal direct current stimulation (tsDCS) is an electro-modulatory tool with possible application in the rehabilitation of spinal cord injury. TsDCS generates a small electric field, aiming to induce lasting, functional neuromodulation in the targeted neuronal networks. Earlier studies have shown significant modulatory effects after application of lumbar tsDCS. However, for clinical application, a better understanding of application specific factors is required. Our goal was to investigate the effect of different electrode configurations using lumbar spinal tsDCS on spinal excitability. We applied tsDCS (2.5mA, 15 minutes) in 10 healthy subjects with three different electrode configurations: 1) Anode and cathode placed over vertebra T11, and the posterior left shoulder respectively (LSC-S) (one polarity), and 2) Both electrodes placed in equal distance (ED) (7cm) above and below vertebra T11, investigated for two polarities (ED-Anodal)/Cathodal). The soleus H-Reflex is measured before, during and after tsDCS in either electrode configuration or a sham condition. To account for genetic predispositions in response to direct current stimulation, subject BDNF genotype was assessed. Stimulation in configuration ED-Cathodal induced an amplitude reduction of the H-reflex, 30 minutes after tsDCS with respect to baseline, whereas none of the other configurations led to significant post intervention effects. BDNF genotype did not correlate with post intervention effects. Furthermore, we failed to replicate effects shown by a previous study, which highlights the need for a better understanding of methodological and subject specific influences on tsDCS outcome. The H-reflex depression after tsDCS (Config. ED-Cathodal) provides new insights and may foster our understanding of the working mechanism of tsDCS.